Fashion and Faith: Islamic Dress and Identity in The Netherlands - Hass, Bat Sheva (Religions, 2019)
This paper focuses on the relationship between clothing and identity-specifically, on Islamic dress as shaping the identity of Dutch Muslim women. How do these Dutch Muslim women shape their identity in a way that it is both Dutch and Muslim? Do they mix Dutch parameters in their Muslim identity, while at the same time intersplicing Islamic principles in their Dutch sense of self? This study is based on two ethnographies conducted in the city of Amsterdam, the first occurring from September to October 2009, and the second took place in August 2018, which combines insights taken from in-depth interviews with Dutch Muslim women and observations in gatherings from Quranic and Religious studies, social gatherings and one-time events, as well as observations in stores for Islamic fashion and museums in Amsterdam. This study takes as its theme clothing and identity, and how Islamic clothing can be mobilized by Dutch Muslim women in service of identity formation. The study takes place in a context, the Netherlands, where Islam is largely considered by the populous as a religion that is oppressive and discriminatory to women. This paper argues that in the context of being Dutch and Muslim, through choice of clothing, these women express their agency: their ability to choose and act in social action, thus pushing the limits of archetypal Dutch identity while simultaneously stretching the meaning of Islam to craft their own identity, one that is influenced by themes of immigration, belongingness, ethnicity, religious knowledge and gender.